A «Risky Area of Business» - the Buffet of the State Duma of the Russian Empire (1906-1917) - Olga Alekseevna Patrikeeva (Управленческое консультирование)
The article is devoted to insufficiently studied page of history of Russian entrepreneurship . The focus of the study - the attempt to device the buffet and the restaurant at the State Duma of the Russian Empire St.Petersburg restaurateurs: A. A. Lomach and T. P. Rumyantsev. A. A. Lomach owned Duma restaurant and bar in the period I and II State Dumas, T. P. Rumyantsev - at the beginning of the III Duma. Despite extensive practical experience, impeccable business reputation A. A. Lomach and T. P. Rumyantsev were unable to achieve success at Russia’s new career. Buffet of the State Duma of the Russian Empire was a «risky area of business». In the dramatic history of this institution, as in a drop of water, reflected the instability of the political life of Russia of the early 20th century, an uneasy way of formation of Russian parliamentarianism. The article is based on the materials stored in the funds of Russian state historical archive, manuscript Department of the Institute of Russian literature of the Russian Academy of Sciences, as well as periodicals of the early twentieth century, the memoirs of contemporaries. The great part of these documents introduced into scientific circulation for the first time.